Effects of Indole-3-Acetic Acid on Germination in Lead Polluted Petri Dish of Citrullus lanatus (Thunberg) Matsumura and Nakai, Cucurbitaceae - Matthew Chidozie Ogwu; Aiwansoba Raymond Osas; Osawaru Moses Edwin (Graduate Program of Syiah Kuala University, 2015)
Watermelon, Citrullus lanatus (Thunberg) Matsumura and Nakai is a tropical fruit vegetable. Indole-3-acetic acid (IAA) is a popular phytohormone while lead (Pb) is a common environmental pollutant in urban and sub-urban centers. C. lanatus were obtained from Benin City with a view to study the effects of IAA on their germination in Pb polluted environment. Germination percentage without IAA and Pb treatment in petri dish was significant after ten days. Hastened germination was observed when IAA and lead were used. About 100 % germination was recorded after seven days. This suggests that water melon seeds can initiate growth even in lead polluted environment. Optimum level of 5 ppm IAA with the different levels of lead treatments may be recommended. Most important was that higher concentrations of Pb in the control (without IAA) did not inhibit seedling shoot nor root growth. Longest seedling shoot length (cm) was 10.33 ± 1.24 and 12.13 ± 2.06 on the seventh and eighth day respectively with the combined treatment levels of 1 ppm IAA and 15 ppm Pb. On the ninth day, 15.27 ± 0.96 was obtained from 1 ppm IAA and 20 ppm Pb. Longest seedling root length (cm) values were recorded from the combined treatment levels of 0 ppm IAA and 10 ppm Pb for the seventh (9.10 ± 0.47) and ninth (10.37 ± 1.81) day respectively and 0 ppm and 15 ppm Pb on the eighth (9.37 ± 0.84) day. Significant means were also obtained with the treatment level of 0 and 20 ppm IAA. This present study suggest the germination of C. lanatus under Pb polluted environment may be rescued with optimum IAA.